Conformational changes in a hyperthermostable glycoside hydrolase: enzymatic activity is a consequence of the loop dynamics and protonation balance - Oliveira, Leandro C. de [UNESP]; Silva, Viviam M. da; Colussi, Francieli; Cabral, Aline D.; Oliveira Neto, Mario de [UNESP]; Squina, Fabio M.; Garcia, Wanius (Public Library Science, 2015)
Endo-beta-1, 4-mannanase from Thermotoga petrophila (TpMan) is a modular hyperthermostable enzyme involved in the degradation of mannan-containing polysaccharides. The degradation of these polysaccharides represents a key step for several industrial applications. Here, as part of a continuing investigation of TpMan, the region corresponding to the GH5 domain (TpManGH5) was characterized as a function of pH and temperature. The results indicated that the enzymatic activity of the TpManGH5 is pH-dependent, with its optimum activity occurring at pH 6. At pH 8, the studies demonstrated that TpManGH5 is a molecule with a nearly spherical tightly packed core displaying negligible flexibility in solution, and with size and shape very similar to crystal structure. However, TpManGH5 experiences an increase in radius of gyration in acidic conditions suggesting expansion of the molecule. Furthermore, at acidic pH values, TpManGH5 showed a less globular shape, probably due to a loop region slightly more expanded and flexible in solution (residues Y88 to A105). In addition, molecular dynamics simulations indicated that conformational changes caused by pH variation did not change the core of the TpManGH5, which means that only the above mentioned loop region presents high degree of fluctuations. The results also suggested that conformational changes of the loop region may facilitate polysaccharide and enzyme interaction. Finally, at pH 6 the results indicated that TpManGH5 is slightly more flexible at 65 degrees C when compared to the same enzyme at 20 degrees C. The biophysical characterization presented here is well correlated with the enzymatic activity and provide new insight into the structural basis for the temperature and pH-dependent activity of the TpManGH5. Also, the data suggest a loop region that provides a starting point for a rational design of biotechnological desired features.